A preconsultation web-based tool to generate an agenda for discussion in diabetes outpatient clinics to improve patient outcomes (DIAT): a feasibility study. Issue 3 (7th March 2017) - Ukoumunne, Obioha C; Vaidya, Bijay; Frost, Julia; Anderson, Rob; Argyle, Catherine; Daly, Mark; Harris-Golesworthy, Faith; Harris, Jim; Gibson, Andy; Ingram, Wendy; Pinkney, Jon; Vickery, Jane; et al.
Abstract : Objective: To test the feasibility of running a randomised controlled trial of a preconsultation web-based intervention (Presenting Asking Checking Expressing (PACE-D)) to improve the quality of care and clinical outcomes in patients with diabetes. Design and setting: A feasibility study (with randomisation) conducted at outpatient diabetes clinics at two secondary care hospitals in Devon, UK. Participants: People with diabetes (type 1 and type 2) attending secondary care general diabetes outpatient clinics. Intervention: The PACE-D, a web-based tool adapted for patients with diabetes to use before their consultation to generate an agenda of topics to discuss with their diabetologist. Outcomes: The percentage of eligible patients who were recruited and the percentage of participants for whom routine glycosylated haemoglobin (HbA1c) data (the putative primary outcome) could be extracted from medical notes and who completed secondary outcome assessments via questionnaire at follow-up were reported. Results: In contrast with the planned recruitment of 120 participants, only 71 participants were randomised during the 7-month recruitment period. This comprised 18.7% (95% CI 14.9% to 23.0%) of those who were eligible. Mean (SD) age of the participants was 56.5 (12.4) years and 66.2% had type 1 diabetes. Thirty-eight patients were randomised to the intervention arm and 33 to the control arm. HbA1c data were available for only 73% (95% CI 61% to 83%) of participants at the 6 months follow-up. The questionnaire-based data were collected for 66% (95% CI 54% to 77%) of the participants at 6 months follow-up. Participants reported that the PACE-D tool was easy to use. Conclusions: A randomised controlled trial of the preconsultation web-based intervention as set out in our current protocol is not feasible without significant modification to improve recruitment and follow-up of participants. The study also provides insights into the feasibility and challenges of conducting complex intervention trials in everyday clinical practice. Trial registration: ISRCTN75070242.